Effectiveness of 980nm diode Laser in reduction the diameters of exposed dentinal tubules for hypersensitive tooth - Hashim, Rana; Dhahir, Mohammed; AlKurtas, Salah A. (Iraqi Journal of Laser, 2023)
Abstracts: Background: The oral cavity is a complex environment, both structurally and functionally, the hard and soft tissues are in close a proximity. Oral tissues subjected to wear throughout the life, that threatened the vitality of the pulp or increase the sensitivity of dentinal tubules. One of the common dental problems is loss of enamel or cementum, which stimulate the nerve ending in or near the pulp and manifested as pain sensation. Aim of the study: This study had done to evaluate the effects of 980nm diode Laser in diameters reduction of exposed dentinal tubules analyze the results and morphological changes of irradiated dentine surface by FE-SEM (field emission scanning electron microscope) analysis.  Material and Method: Thirty-nine human extracted impacted 3rd molar teeth were tested in this study and divided into control Group (N=15), pilot study (N=9) and study group (N=15).  The study group irradiated with 980nm diode Laser to the occlusal surface of the teeth after the application of 17% EDTA (Ethelyn diamine tetra acetic acid) for smear layer removal. The intra-pulpal temperature recorded for every second and monitored for 120s from the first second of irradiation by a thermometer (prośket MT-1820, 1st Edition, 2016, Taiwan), for detection the recovery time of initial tooth temperature.  FE-SEM analysis to all teeth (control, pilot and study groups) for assessment the morphological changes after surface irradiation. Results: FE-SEM analysis to the irradiated surface show significant reduction in diameters of the exposed dentinal tubules irradiated by 980nm diode Laser. Conclusion: The selected parameters (1.5W/10s, 276.3W/cm2) were able to seal exposed dentinal tubules without any sign of cracks or fissures. Suggestion: The parameters used with this study (1.5W, 10s, 276.3W/cm2) can be utilize in the future treatment protocol to the management of dentinal hypersensitivity.